Combined targeting of G protein‐coupled receptor and EGF receptor signaling overcomes resistance to PI3K pathway inhibitors in PTEN‐null triple negative breast cancer. Issue 8 (16th July 2020) - Zecchin, Davide; Moore, Christopher; Michailidis, Fanourios; Horswell, Stuart; Rana, Sareena; Howell, Michael; Downward, Julian
Abstract: Triple‐negative breast cancer (TNBC) has poorer prognosis compared to other types of breast cancers due to the lack of effective therapies and markers for patient stratification. Loss of PTEN tumor suppressor gene expression is a frequent event in TNBC, resulting in over‐activation of the PI 3‐kinase (PI3K) pathway and sensitivity to its inhibition. However, PI3K pathway inhibitors show limited efficacy as monotherapies on these tumors. We report a whole‐genome screen to identify targets whose inhibition enhanced the effects of different PI3K pathway inhibitors on PTEN‐null TNBC. This identified a signaling network that relies on both the G protein‐coupled receptor for thrombin (PAR1/F2R) and downstream G protein βγ subunits and also epidermal growth factor receptor (EGFR) for the activation of the PI3K isoform p110β and AKT. Compensation mechanisms involving these two branches of the pathway could bypass PI3K blockade, but combination targeting of both EGFR and PI3Kβ suppressed ribosomal protein S6 phosphorylation and exerted anti‐tumor activity both in vitro and in vivo, suggesting a new potential therapeutic strategy for PTEN‐null TNBC. Synopsis: PTEN‐null triple negative breast cancers (TNBC) show sensitivity to drugs targeting PI3K pathway, and especially PI3Kβ. However, these compounds demonstrated limited efficacy in the clinic. Identification of mechanisms that impair response of these tumours to PI3K pathway inhibitors is urgently needed. EGFR was shown to signal to PI3Kβ and its activity limited the response to PI3Kβ inhibition. The G‐protein coupled receptor PAR1 activated PI3Kβ‐AKT through the βγ subunit of G protein. Combined inhibition of PI3Kβ and EGFR produced anti‐tumour activity both in vitro and in vivo in PTEN‐null TNBCs and resulted in sustained suppression of the downstream marker phospho‐S6. Abstract : PTEN‐null triple negative breast cancers (TNBC) show sensitivity to drugs targeting PI3K pathway, and especially PI3Kβ. However, these compounds demonstrated limited efficacy in the clinic. Identification of mechanisms that impair response of these tumours to PI3K pathway inhibitors is urgently needed.